Coverage of Women’s Agricultural Activities in Nigerian Daily Newspapers - O P Fawole; T A Olowu (Journal of Agricultural Extension, 2015)
This study investigated the coverage and direction of women's agricultural activities in Nigerian daily newspapers between 1970 and 1990. In order to attain the research objectives, 6408 editions 10 daily newspapers were randomly selected for the 21-year period. These newspaper editions were content analysedfor types of women activities reportedandprominence anddirection of the reportedactivities. The results indicate that there has been a steady increase in the number of women's agricultural activities reportedin Nigerian dailies. While the amount of space allocated to women’s activities is small, the reports are favourable but not prominently located.